Comprehending Agent and Agentless Types of English Active and Passive Voice by Indonesian Learners of English - Ratna Puspitasari (Universitas Pendidikan Indonesia (UPI), 2016)
The study entitled “Comprehending Agent and Agentless Types of English Active and Passive Voice by Indonesian Learners of English” aims to analyze and describe how Indonesians as English learners comprehend agent and agentless types of English active and passive sentences, and to uncover the factors affecting comprehension. The participants of the study were 26 university students from a grammar class of 2015. The two main instruments used were an individual test and a set of questionnaires for personal information. Participants’ performances in the test regarding the agent and agentless types of English active and passive voices were correlated with their personal data which contain aspects affecting their learning of second language. The mean score and percentage of individual result of the test were used to determine the sentences that received the highest and the lowest performances. Two major ways were discovered that help participants comprehend those types of active and passive voices, namely identifying the items in sentences and selecting explicit choices. L1 interference is shown to have significant relations to the participants’ comprehension of agent and agentless types of English active and passive sentences, especially the interference in the structure of sentences and grammatical error. In addition to L1 interference, the factors that were taken into account to contribute to the comprehension, were individual differences. The findings of this study were assessed by using appropriate and relevant linguistic theories. Keywords: Second language learning, agent and agentless types of active and passive voice, L1 interference, Individual differences